Caribbean Report 16-03-1989 - Croskill, Hugh (anchor); Hagan, Pat (interviewee); Pipe, Roger (interviewee); Wareni, Frank (interviewee); Patrick, Soraya (correspondent); Green, Simeon (interviewee); Warner, Elston (interviewee); Bennish, Peter (correspondent) (The British Broadcasting Corporation, 1989)
Contrary to statements made by the Grenada Co-operative Nutmeg Association, the agreement has been breached. Pat Hagan, editor of Commodity Week confirmed that Indonesia is selling nutmeg at reduced prices. Democratic Congressman, Frank Guarini commented favourably on Prime Minister, Michael Manley's trip to the United States. In Britain, a group calling itself the Black Liberation Front is calling on the resignation of Chief Constable, Geoffrey Dear. Members of the black community are not convinced. Simon Hinds of the Voice Newspaper noted that circumstantial evidence points to a white group to discredit the black community and acting as political foot soldiers. The Canadian enquiry into drug use by amateur athletes continues with the testimony of Tony Issajenko, husband of Angela Taylor-Issajenko.
1. Headlines (00:00-00:51)
2. Interview with Roger Pipe, Managing Director of Rocker and Sland, a British spice company on the collapse of the nutmeg cartel, Indonesia and Grenada (00:52-05:42)
3. Interview with Frank Wareni, Democratic Congressman on Michael Manley's visit to Washington (05:43-08:45)
4. Financial News (08:46-10:08)
Keywords: Manley, Michael.; Racism.; Nutmeg industry -- Grenada.; Nutmeg industry -- Indonesia.; Price cutting -- Indonesia.; Cartels -- Grenada.; Cartels -- Indonesia.; United States -- Foreign relations -- Jamaica.; United States -- Foreign economic relations -- Jamaica.; Race relations.; Racism -- United Kingdom.; Police -- United Kingdom.; Doping in sports -- Canada.; Sports -- Corrupt practices -- Canada.; Sports -- Drug use -- Canada.; James, Norris.; Grenada Co-operative Nutmeg Association.; Issajenko, Tony.